Polarimetry of the cosmic microwave background from the antarctic plateau - SIRONI, GIORGIO; Battistelli, E; BOELLA, GIULIANO FILIPPO; Cavaliere, F; GERVASI, MASSIMO; PASSERINI, ANDREA; Spiga, D; ZANNONI, MARIO (Publications of the Astronomical Society of Australia, 2002)
Detection of linear polarisation at a level of 1 ppm or less, associated to the anisotropy of the cosmic microwave background, will confirm the cosmological origin of the observed anisotropy and provide information on the thermal history of the universe between the recombination epoch and now. In particular, detection of polarisation can help in deciding if the evolution of the universe included a reionisation epoch. We present the Mk3 model of our correlation polarimeter, an improved version of a system which has already been used for observations of the region of sky around the South Celestial Pole from Antarctica (in 1994 at Terra Nova Bay and in 1998 at Dome C)